Endometrial cancer in the elderly: does age influence surgical treatments, outcomes, and prognosis?. Issue 9 (September 2018) - Koual, Meriem; Ngo, Charlotte; Girault, Aude; Lécuru, Fabrice; Bats, Anne-Sophie
Abstract: Objective: To compare clinicopathological characteristics, surgical outcomes, and survival rates for nonelderly (<75 years old) and elderly (≥75 years old) women with endometrial cancer (EC). Methods: This retrospective study included consecutive patients who underwent surgery for EC at the gynecologic-oncologic surgery department of Hôpital Européen Georges-Pompidou (Paris, France) from January, 2002 to December, 2015. Independent-group t tests and chi-square tests were used to compare elderly and nonelderly women. Survival rates were compared using log-rank (Mantel-Cox) tests. Results: In the nonelderly and elderly groups, the mean age at EC diagnosis was 63 (range 33-74) and 81 (range 75-95) years, respectively. Compared with nonelderly patients, elderly patients (n = 104) presented with more advanced disease and more aggressive histological findings. However, surgical approaches did not differ between the two groups, and 76% of all patients underwent minimally invasive surgery. Pelvic lymphadenectomy was performed in 65% and 44% of nonelderly and elderly patients, respectively ( P  = 0.01), whereas para-aortic lymphadenectomy was performed in 26% and 9% of nonelderly and elderly patients, respectively ( P  < 0.0001). The incidence of perioperative complications was almost the same in the elderly and nonelderly groups. The 5-year disease-free survival rate was higher in the nonelderly group ( P  = 0.023), and the 5-year cancer-specific mortality rate was higher in the elderly group ( P  = 0.042). Conclusions: Although elderly patients present with cancers that are more aggressive, the management of EC in this population is not optimal. Further clinical studies need to be conducted for elderly women with EC, and specific treatment guidelines should be developed to improve their prognosis. Abstract : Supplemental Digital Content is available in the text